1997
DOI: 10.1161/01.hyp.30.3.428
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Pressure Control on Progressive Renal Disease in Blacks and Whites

Abstract: African Americans (blacks) have a disproportionately high incidence of end-stage renal disease due to hypertension. The Modification of Diet in Renal Disease (MDRD) Study found that strict blood pressure control slowed the decline in glomerular filtration rate (GFR) only in the subgroup of patients with proteinuria. The present report compares the effects of blood pressure control in black and white MDRD Study participants. Fifty-three black and 495 white participants with baseline GFRs of 25 to 55 mL/min/1.73… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
79
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(85 citation statements)
references
References 35 publications
3
79
0
3
Order By: Relevance
“…A target of Ͻ135/75 mmHg is recommended by the National Institutes of Clinical Excellence (17). Moreover, data from the Modification of Diet in Renal Disease Study Group suggest an even lower target BP of Ͻ120/70 mmHg to limit progressive renal disease (25). In our study, the level of albuminuria was unaffected by BP lowering.…”
Section: Statisticssupporting
confidence: 45%
“…A target of Ͻ135/75 mmHg is recommended by the National Institutes of Clinical Excellence (17). Moreover, data from the Modification of Diet in Renal Disease Study Group suggest an even lower target BP of Ͻ120/70 mmHg to limit progressive renal disease (25). In our study, the level of albuminuria was unaffected by BP lowering.…”
Section: Statisticssupporting
confidence: 45%
“…This is particularly important in light of evidence that lower BP goals have been shown to provide greater cardiovascular and renal benefits in numerous clinical trials in patients with diabetes and renal disease. [24][25][26] In addition to demonstrating the superior rate of BP goal achievement with olmesartan medoxomil, this study demonstrated that numerically fewer reported oedema-related AEs were associated with olmesartan medoxomil compared with amlodipine when both drugs are administered at the recommended starting doses. It has been well established that many patients require dose titration in order to reach an appropriate BP target.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, low BP treatment goal showing greater benefit in those with proteinuria exceeding 3g per day at baseline, moderate in those with proteinuria between 1 and 3g per day, and no benefit in those with proteinuria of less than 1g per day [7]. These post hoc analysis findings led to the Post hoc analysis suggested that a lower BP target might be more effective in preventing renal disease progression in black versus white patients [9] and that blacks have higher nocturnal BP and may benefit from greater nocturnal BP lowering [10]. Furthermore, a follow up analysis of the MDRD cohort for 7 years revealed fewer ESRD or combined ESRD and death events in the more aggressive BP lowering group [11].…”
Section: Modification Of Diet In Renal Disease Studymentioning
confidence: 99%